DNA barcoding as a regulatory tool for seafood authentication in Canada. (October 2018) - Shehata, Hanan R.; Naaum, Amanda M.; Garduño, Rafael A.; Hanner, Robert
Abstract: Since 2013, DNA barcoding has been in use by the Canadian Food Inspection Agency (CFIA) to speciate finfish fillets sold and consumed in Canada. We retrospectively assessed both the usefulness of DNA barcoding technology as a regulatory tool and the usefulness of the publicly available Barcode of Life Database (BOLD) in supporting the application of this technology. Speciation results for 354 finfish products collected from across Canada between 2013 and 2016 as part of the routine inspections and sampling plans of the CFIA were analyzed to determine the success rate of positive identification, and the level of mislabelling. The overall success rate was 93.2%. The rate of mislabelling was 14.8%, which is in the low end of mislabelling rates reported in the literature. Among the mislabelled samples, there was a case where an endangered species (IUCN Red List) was sold under another name. DNA barcoding as applied by the CFIA identified mislabelled seafood products in Canada. We also conducted a gap analysis comparing public DNA barcode sequences in BOLD against the seafood species listed in the CFIA "Fish List". As of March 26th, 2018, 67 species names out of 829 unique species names on the CFIA Fish List were not associated with any records in BOLD. To best support CFIA's regulatory application of DNA barcoding, BOLD could be improved by the addition of taxonomically authenticated sequences for the 67 species lacking barcoding data, and by maintaining a collection of sequences exclusively for use in regulatory testing. Highlights: We evaluated use of DNA barcoding and Barcode of Life Database, as a regulatory tool. 67 of the species on the CFIA Fish List have no records on Barcode of Life Database. DNA barcoding of 354 seafood samples from Canada revealed 14.8% mislabelling rate. One instance of an endangered species substituted under another name was found. It is recommended to develop a sequence database for use for regulatory purposes.